1982
DOI: 10.2527/jas1982.55138x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Nutritional Status of Beef Cattle Herds from Four Soil Order Regions of Florida. II. Trace Minerals

Abstract: An experiment was conducted to determine the trace mineral status of grazing cattle from four selected soil type regions in Florida. Animal tissue, forage and soil samples were collected during the wet (September-October) and dry (February-March) seasons from nine ranches located in four different regions. On the basis of reported critical forage levels, mean forage Co (less than .1 ppm), Zn (less than 30 ppm) and Se (less than .1 ppm) and liver and hair Se (less than .25 ppm), were low during both seasons. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
4

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
3
1
4
Order By: Relevance
“…Forage Mo levels determined in our study were well below the toxic level (6 mg/kg) as suggested by McDowell [16]. Our results for forage Mo clearly agree with the findings reported by McDowell et al [20] and Merkel et al [21] in Florida. Hornick et al [18] have suggested a guideline value of up to 50 mg Mo/kg for most agricultural soils.…”
Section: Foragesupporting
confidence: 94%
“…Forage Mo levels determined in our study were well below the toxic level (6 mg/kg) as suggested by McDowell [16]. Our results for forage Mo clearly agree with the findings reported by McDowell et al [20] and Merkel et al [21] in Florida. Hornick et al [18] have suggested a guideline value of up to 50 mg Mo/kg for most agricultural soils.…”
Section: Foragesupporting
confidence: 94%
“…Forage Zn concentration may be high up to 458.7 µmol kg -1 (NRC 1984), but its level decreases rapidly as plant matures, and decreases to a considerably lower level (McDowell et al, 1982). Similar results have been found in our investigation.…”
Section: Husksupporting
confidence: 91%
“…It could be deduced that plants absorbed quite high levels of Se from soil of the study area. McDowell et al [23]and Khan et al [12] obtained lower values for Se in plants compared to the current study whereas, similar observations have been reported in Colombia [24] and Pakistan [11,25].…”
Section: Mineral Analysis Soilsupporting
confidence: 85%